Disiplin Diri dan Manajemen Waktu dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam - Didit Darmawan; Dzakiyatul Fuada (Simpati, 2026)
This study conducts a qualitative literature review on students' awareness in following school rules as a reflection of high internal motivation forming self-discipline without pressure, and examines the influence of time management discipline on the effectiveness of achieving Islamic Education learning outcomes. The analysis reveals that awareness in following rules develops through a long process of value internalization, starting from external compliance due to fear of punishment, shifting to compliance due to understanding the benefits of rules, and finally reaching a stage where rules are followed because their values have merged with self-identity. Factors such as dialogical rule socialization, teacher role modeling, conducive social environment, educational sanction systems, and consistent implementation significantly determine the success of this internalization. Meanwhile, time management discipline significantly influences the effectiveness of Islamic Education learning outcomes. Students with time management skills can organize study schedules, allocate time for reflection and appreciation of religious material, and consistently perform worship. The impact is seen not only in cognitive aspects through academic grades, but also in affective aspects through religious awareness and psychomotor aspects through regular worship behavior. These findings imply the need for schools to shift disciplinary development paradigms from authoritarian approaches focused on supervision and punishment toward humanist approaches focused on value internalization.